Dental Amalgam- Anthropogenic Aspects - Pragya Pandey; Kirti Srivastava; Himanshu Reddy; Diksha Singh (Institute of Medico-legal Publications Pvt Ltd, 2021)
Mercury is released in the environment by various natural and anthropogenic activities. As mercury is toxic, presence of high levels of mercury in the environment is a major concern. One source of mercury in humans is dental amalgam fillings. Dental amalgam has been used for ages in dental clinics and dental hospitals for restoring defective and decayed teeth. This raises concern regarding the use of dental amalgam and its disposal. The purpose of this article is to sensitize people about the hazards of mercury, make them cognizant with guidelines regarding the use of mercury in dental clinics and enforce the use of alternatives to mercury when possible.